Extensive Research Does Not Imply Extensive Funding - Alexander Eickelpasch; Christoph Grenzmann (Weekly Report, 2009)
In Germany, two statistics examine the development and structure of public funding for research and development (R&D) in the private sector of the economy: the R&D statistics of the so-called "Stifterverband für die deutsche Wissenschaft - SV", a joint initiative of German industries to promote science an higher education (SV), and, secondly, the statistics of the "Bundesministerium für Bildung und Forschung, BMBF" (German Federal Ministry of Education and Research)) on "Federal Government expenditure on science, research and development to business enterprises". Based on these two sources, our weekly report provides an overview of the allocation of public R&D funding. The results highlight the fact that some research-intensive sectors-such as the manufacture of aircraft and spacecraft-benefit from disproportionately large amounts of federal state funding. Other, equally R&D-intensive business segments, such as the chemical industry receive a significantly lower proportion of public R&D grants. Generally speaking, smaller companies can expect greater support than large companies. This inequality in funding rates reflects the focus of research and innovation policy on particular company sizes or fields of technology. The second part of the report discusses the quality of the available data on the distribution of R&D funding. Considering the disparities between degree of coverage, consistency and timescale of the two statistics in question, the current state of available information remains unsatisfactory and requires further refinement.
Keywords: O32; O38; 330; Research and Development; Funding